Extracorporeal therapy procedures (plasma exchange and immunoadsorption) in chronic inflammatory demyelinating polyneuropathies (CIDP)– a database analysis - Moritz Mahlberg; Johannes Dorst; Zeynep Elmas; Ulrike Haase; Michael Heming; Louisa Müller-Miny; Gerd Meyer zu Hörste; Mark Stettner; Florian Then Bergh; Petra Baum; on behalf of the Disease-Related Competence Network Peripheral Nervous System (KKPNS) (BMC Neurology)
Abstract Background and objectives There is limited study data on both therapeutic plasma exchange (PE) and immunoadsorption (IA) in chronic inflammatory demyelinating polyneuropathy (CIDP), mostly based on case series in patients in the early stages of the disease. The aim of this retrospective study was to compare the efficacy and tolerability of the two therapy procedures in a larger sample with a longer duration of disease and immunomodulatory pre-treatment. Methods In this retrospective study from 5 centers in Germany, register data on the efficacy, safety and tolerability of therapy with IA or PE in patients with CIDP were examined. Treatment response was assessed using neurological scores (INCAT and Hughes Score), duration of hospital stay, and subjective assessment by examiners and patients. In addition, side effects were recorded. Results A total of 44 patients were analyzed, 23 treated with PE (mean age 61.3 years, 17 male, 6 female) and 21 with IA (mean age 67, 14 male, 7 female). The mean duration of disease before treatment was 8.48±3.82 years (PE group) and 7.24±3.15 years (IA group). IA and PE showed a comparable treatment response. With IA, 11 out of 21 (52.4%) patients improved, whereas with PE, 14 out of 23 (60.9%) patients improved. The differences between before- and after-treatment INCAT and Hughes scores also showed an improvement with both PE and IA individually (INCAT 1.17±1.61 and 0.71±1.65, respectively, Hughes score 0.48±0.73 and 0.33±0.66, respectively), while there were no significant differences between the two groups. The patients in the IA group had a significantly shorter inpatient stay (p < 0.019). There was one adverse event in each group, but no serious adverse events in either group. Discussion This retrospective study indicates that IA and PE show comparable efficacy in chronic autoimmune neuropathies, including patients with longer disease duration and immunomodulatory pretreatment.